OC-037 6 year disease durability outcomes on patients treated with endoscopic therapy for barrett's related neoplasia from the uk registry. (22nd June 2015) - Haidry, R; Lipman, G; Gupta, A; Dunn, J; Smart, H; Bhandari, P; Willert, R; Fullarton, G; di Pietro, M; Gordon, C; Penman, I; Boger, P; et al.
Abstract : Introduction: Endoscopic therapy with combined Endoscopic mucosal resection (EMR) followed by Radiofrequency ablation (RFA) is now the recommended first line treatment for patients with Barrett's (BE) related neoplasia confined to the oesophageal mucosa. Method: We examine prospective data from the United Kingdom registry of patients undergoing RFA/EMR for BE neoplasia since 2008. Before RFA, visible lesions and nodularity were entirely removed by EMR. Thereafter patients underwent RFA 3 monthly until all visible BE was ablated or cancer developed (endpoints). Biopsies were taken at 12 months or when endpoints reached. Follow up endoscopies were performed periodically in all patients to check for recurrences thereafter. All patients who had completed at least 12 months of follow up after successful treatment were included in the analysis to examine durability of disease reversal long term. Results: 282 patients (81% male, mean age 70 years) have completed the 12 month treatment protocol with a minimum of 12 months follow up thereafter. At median follow up of 37 months (IQR 29–49), 93% of patients with successful disease reversal were still free of neoplasia and 88% free of intestinal metaplasia recurrence. Cancer progression at this same time was seen in 1.4% of patients. Kaplan Meier (KM) statistics demonstrated a predicted 3 year neoplasia free survival in 88% of patients. At 5 and 6 years this was 86%. Similarly KM analysis showed that at 3 years 81% of patients would be free form BE and at 5 and 6 years this figure was 73%. Conclusion: We report long term outcomes of a large cohort of patients with BE neoplasia who have had successful endoscopic therapy with RFA/EMR. This approach appears to have a lasting disease free benefit in the majority of patients. Recurrences do occur in a minority of patients and highlights the need for follow up in those fit for endoscopy. All collaborators of the UK RFA registry are acknowledged for their contributions to data collection for this work . Disclosure of interest: None Declared.